2018
DOI: 10.1080/14756366.2018.1530994
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and cytotoxic activities of novel copper and silver complexes of 1,3-diaryltriazene-substituted sulfonamides

Abstract: In this study, a series of 10 novel copper (II) and silver complexes of 1,3-diaryltriazene-substituted sulfonamides was synthesised. All the synthesised ligands and their metal complexes were assessed for in vitro cytotoxicity against human colorectal adenocarcinoma (DLD-1), cervix carcinoma (HeLa), breast adenocarcinoma (MDA-MB-231), colon adenocarcinoma (HT-29), endometrial adenocarcinoma (ECC-1), prostate cancer (DU-145 and PC-3), normal embryonic kidney (HEK-293), normal prostate epithelium (PNT-1A), and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…[31] In a previous study, a series of aromatic and heterocyclic bis-sulfonamide Schiff bases against hCA I, II, VII, and IX was investigated, and many of the compounds showed a low nanomolar potency against hCA II, with K I values in the range of 0.4-861.1 nM. [32] In the present study, a series of novel, structurally diverse ST1-11 was synthesized as a modified procedure presented in our previous studies [3,25,26] and outlined in Scheme 1. Briefly, the diazonium salt of ST was obtained by using sodium nitrite solution in the The use of inhibitor compounds for various hCA isozymes is well established for the management of elevated intraocular pressure, hypertension, memory impairments, depression, arteriosclerosis, epilepsy, obesity, and hypoxic cancers.…”
Section: Drug Design Strategy and Chemistrymentioning
confidence: 91%
See 1 more Smart Citation
“…[31] In a previous study, a series of aromatic and heterocyclic bis-sulfonamide Schiff bases against hCA I, II, VII, and IX was investigated, and many of the compounds showed a low nanomolar potency against hCA II, with K I values in the range of 0.4-861.1 nM. [32] In the present study, a series of novel, structurally diverse ST1-11 was synthesized as a modified procedure presented in our previous studies [3,25,26] and outlined in Scheme 1. Briefly, the diazonium salt of ST was obtained by using sodium nitrite solution in the The use of inhibitor compounds for various hCA isozymes is well established for the management of elevated intraocular pressure, hypertension, memory impairments, depression, arteriosclerosis, epilepsy, obesity, and hypoxic cancers.…”
Section: Drug Design Strategy and Chemistrymentioning
confidence: 91%
“…is based on our most recent studies, in which we indicated that novel synthesized 1,3-diaryltriazene-substituted sulphanilamide and metanilamide derivatives have a potent and selective inhibition against one of the most abundant isoform hCA II. [3,25,26] Therefore, in the current work, our aim was to change the sulfonamide group from primary to secondary amine and apply it to hCA I, hCA II, AChE, and α-GLY enzymes, [27][28][29] to see the effect of the binding group against potency and selectivity. We aimed to improve the biological potency of 1,3-dirayltriazene-substituted sulfonamides by changing the amine part from primary to secondary (sulphanilamide to sulfathiazole) and observing the potency of these type of compounds against different metabolic enzymes rather than hCA I and II, such as AChE and α-GLY.…”
Section: Drug Design Strategy and Chemistrymentioning
confidence: 99%
“…CA inhibition assay was done as described in our previous studies by using an esterase assay with 4-nitrophenyl acetate as standard [21][22][23][24][25][26][27][28][29][30][31] . The enzymes were purified from human blood as described earlier 27,28 .…”
Section: Carbonic Anhydrase Inhibition Assaymentioning
confidence: 99%
“…They can be divided into five classes: Ag(I)-NHC complexes, Ag(I) -carboxylate complexes, Ag(I) -N-ligand complexes, Ag(I)-P-ligand complexes and mixed Ag(I) ligand complexes. These were tested against several tumour lines (e.g., kidney cancer [18][19][20][21][22], breast cancer MCF-7 [23][24][25], colorectal cancer (HCT 116) [20], lung cell lines A549 [26] tongue cancer (Cale27), HepG2, and renal adenocarcinoma (Ae498)) and in three murine cell lines (P815 mastocytoma, B16 melanoma, P388 leukaemia) [27][28][29]. The cytotoxicity in the abovementioned articles was determined mainly by the MTT assay, but studies of mechanism of action (interaction with ctDNA, DNA nuclease activity, effect on topoisomerase I/II, cell cycle, mitochondrial membrane potential, lipophilicity, cell morphology studies, induction of oxidative stress) are not often performed.…”
Section: Introductionmentioning
confidence: 99%